2020
DOI: 10.2147/dmso.s236127
|View full text |Cite
|
Sign up to set email alerts
|

<p>The Role of JNk Signaling Pathway in Obesity-Driven Insulin Resistance</p>

Abstract: Obesity is not only closely related to insulin resistance but is one of the main factors leading to the formation of Type 2 Diabetes (T2D) too. The c-Jun N-terminal kinase (JNK) family is a member of the mitogen-activated protein kinase (MAPK) superfamily. JNK is also one of the most investigated signal transducers in obesity and insulin resistance. JNK-centric JNK signaling pathway can be activated by growth factors, cytokines, stress responses, and other factors. Many researches have identified that the acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
43
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(44 citation statements)
references
References 54 publications
(59 reference statements)
0
43
0
1
Order By: Relevance
“…Interestingly, many researchers have demonstrated that obese subjects show an activated phosphorylation of JNK that negatively regulates the insulin signalling pathway. Indeed, upon activation, JNK is translocated from the cytoplasm into the nucleus, thus promoting the expression of several pro-inflammatory genes and protein synthesis (e.g., IL-1β, TNFα, IL-8, and IL-6), impairing glucose tolerance by obesity-induced insulin resistance [ 72 ]. Similarly, inappropriately increased activation of p38 MAPK has been suggested to contribute to insulin resistance by downregulating the expression of the insulin-responsive glucose transporter (GLUT4) and, in turn, reducing insulin-stimulated glucose uptake [ 73 ].…”
Section: Phytosterols In Human Nutritionmentioning
confidence: 99%
“…Interestingly, many researchers have demonstrated that obese subjects show an activated phosphorylation of JNK that negatively regulates the insulin signalling pathway. Indeed, upon activation, JNK is translocated from the cytoplasm into the nucleus, thus promoting the expression of several pro-inflammatory genes and protein synthesis (e.g., IL-1β, TNFα, IL-8, and IL-6), impairing glucose tolerance by obesity-induced insulin resistance [ 72 ]. Similarly, inappropriately increased activation of p38 MAPK has been suggested to contribute to insulin resistance by downregulating the expression of the insulin-responsive glucose transporter (GLUT4) and, in turn, reducing insulin-stimulated glucose uptake [ 73 ].…”
Section: Phytosterols In Human Nutritionmentioning
confidence: 99%
“…When ERS was overactivated, in addition to downstream XBP1 inhibition and IRE1α/JNK pathway activation, the induction of apoptosis was observed. Previous studies have demonstrated that JNK-induced apoptosis is an important cause of several diseases, including cancer, liver dysfunction, metabolic disorders and neurodegenerative diseases (38)(39)(40)(41). The apoptosis of lung epithelial cells is an important mechanism of BPD (1).…”
Section: Discussionmentioning
confidence: 99%
“…In the context of obesity, JNK pathways can be activated by proinflammatory cytokines, FFA and reactive oxygen species (ROS), and regulate several nuclear and extra-nuclear substrates, specially the transcription factor activator protein 1 (AP1) which controls the expression of proinflammatory genes and protein synthesis ( e.g. TNF-α, IL-1β, IL-6 and IL-8) ( Pal et al., 2016 ; Feng et al., 2020 ). Deregulated activation of NF-κB and JNK pathways results in increased transcription of IL-6 and TNF-α, which reduce the sensitivity of insulin target cells towards insulin.…”
Section: Pathogenesis Of Metsmentioning
confidence: 99%